Pemanfaatan Kesenian Sakeco Etnis Samawa Sebagai Materi Pembelajaran Sastra di SMP - Sukiman Sukiman (Universitas Hamzanwadi, 2018)
Writing this article aims to describe the use of Samawa sakeco ethnic as a source of literary learning materials in junior high. Sakeco can be used as a source of literature learning especially in SMP. Local wisdom as a wealth of archipelago can be used for learning resources in schools. The use of learning resources close to the students will help teachers achieve learning objectives. One form of local wisdom in Sumbawa is sakeco. Sakeco is a form of submission of old poetry most popular by the people of Sumbawa.